Displaced archives: a mapping review: a mapping review - Ascensão de Macedo, L. S. (2019)
This article realises a mapping review on the topic “displaced archives”. The main problem is concerned to the absence of a clear conceptual framework about this topic, existing several terms related to the same phenomenon. The purpose of this paper is to explore the literature in terms of characteristics and size, identifying main concepts, theories, sources and knowledge gaps. Searches were performed in the Web of Science database. As inclusion criteria, we extracted terms from archival terminology in English and scientific articles published between 1953 and 2018 in peer reviewed journals. Methodologically, the article combines mapping review with a scoping review. Of the 160 articles, 70 were included, published between 1962 and 2018. Themes associated with decolonization and secession, armed conflict and illicit trafficking predominate, related to international and sub-national issues. Qualitative studies, especially historical analysis and case studies, prevail. New concepts such as colonial archives, seized archives and expatriate archives that are not considered in archival terminography are emerging. To conclude, the concept of "displaced archives" remains invisible to the archival community, especially the lusophone archival community, that no scientific production on the topic was retrieved.